Case report of vulval/labial leiomyoma - A rare pathological entity - Gayam, Susheela; Tallavajhula, Mythili (Indian Journal of Case Reports, 2020)
Leiomyomas are benign smooth muscle tumors. They can develop anywhere in the body, but the most common site is the uterine myometrium. The vulval leiomyomas are rare in occurrence and are uncommon. We report a case of a 33-year-old woman who presented with a painless vulval mass for 3 years. The histopathological examination following its surgical removal was indicative of leiomyoma which was positive for smooth muscle actin.